2020
DOI: 10.1021/acs.jpca.0c03254
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Treatment on Alkylation of a Functionalized Deltahedral Zintl Cluster

Abstract: Density functional theory (DFT) is one of the popular methods to understand the electronic structure of molecular systems based on electronic density. On the basis of this theory, several conceptual DFT descriptors have been developed which can deal with the stability, reactivity, and several other physicochemical properties of molecules. Here, we have taken a nine-atom-functionalized deltahedral Zintl cluster of germanium (Ge) to examine the alkylation reaction mechanism. The study showed that the Zintl clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In this regard, we thought of a new type of Lewis base i. e., Zintl Lewis base, which can also be used as a nucleophile in S N 2 reaction. [23][24][25] Zintl cluster is polyatomic versatile multianion species belong to a main group compound that exhibits unique reactivity and can participate in diverse chemical transformations. [26][27][28][29][30][31][32] Recently, various studies shown that the nonagermanium based Zintl cluster (Ge 9 ) can be act as a nucleophile due to its presence of external lone pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we thought of a new type of Lewis base i. e., Zintl Lewis base, which can also be used as a nucleophile in S N 2 reaction. [23][24][25] Zintl cluster is polyatomic versatile multianion species belong to a main group compound that exhibits unique reactivity and can participate in diverse chemical transformations. [26][27][28][29][30][31][32] Recently, various studies shown that the nonagermanium based Zintl cluster (Ge 9 ) can be act as a nucleophile due to its presence of external lone pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is evident that nucleophile agent can be a great reagent for the disulfide bond cleavage. In this regard, we thought of a new type of Lewis base i. e., Zintl Lewis base, which can also be used as a nucleophile in S N 2 reaction [23–25] …”
Section: Introductionmentioning
confidence: 99%